LITERASI KEUANGAN MEMEDIASI PENGARUH PENDAPATAN, RETURN DAN RISIKO TERHADAP KEPUTUSAN INVESTASI PADA MAHASISWA (Studi Pada Mahasiswa yang Berinvestasi di Galeri Investasi UIN Suska Riau, Universitas Riau dan Universitas Muhammadiyah Riau) - SURYADI, NANDA; YUSNELLY, ARIE; SEPTI RAHAYU, YOLANDA (JURNAL AKUNTANSI DAN KEUANGAN, 2023)
This study aims to see the effect of income, return, risk and financial literacy on investment decisions in students (Study on Students Investing in UIN Suska Riau Investment Gallery, UNRI Investment Gallery, and UMRI Investment Gallery with financial literacy as a mediating variable. This type of research is quantitative research. The data collection method uses a questionnaire. The population in this study amounted to 2312 students. The sampling technique used probability sampling technique by means of simple random sampling with a sample of 200 respondents. The results of this study indicate that income has a significant effect on investment decisions in students; return has a significant effect on investment decisions in students; risk has a significant effect on investment decisions in students; financial literacy has a significant effect on investment decisions in students; income has significant effect on financial literacy; financial literacy can mediate income on investment decisions in students.